2012
DOI: 10.1002/jcp.24129
|View full text |Cite
|
Sign up to set email alerts
|

Homeodomain‐interacting protein kinase2 in human idiopathic pulmonary fibrosis

Abstract: Homeodomain-interacting protein kinase 2 (Hipk2) is an emerging player in cell response to genotoxic agents that contributes to the cell's decision between cell cycle arrest or apoptosis. HIPK2 acts as co-regulator of an increasing number of transcription factors and modulates many different basic cellular processes such as apoptosis, proliferation, DNA damage response, differentiation. Idiopathic pulmonary fibrosis (IPF) is characterized by an anatomical disarrangement of the lung due to fibroblast proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 42 publications
(51 reference statements)
2
26
0
Order By: Relevance
“…Small airway obstruction was detect in 76.1% (86/113) of the pSS patients. However, there were no significant differences in the MEF 25 , MEF 50 and MEF 75 values between the two groups.…”
Section: Pulmonary Function Testsmentioning
confidence: 67%
See 2 more Smart Citations
“…Small airway obstruction was detect in 76.1% (86/113) of the pSS patients. However, there were no significant differences in the MEF 25 , MEF 50 and MEF 75 values between the two groups.…”
Section: Pulmonary Function Testsmentioning
confidence: 67%
“…Studies revealed mechanistic links between aging and lung fibrosis involving telomere attrition, genomic instability, and epigenetic alterations (24)(25)(26). Antihistone antibodies, a type of ANA, are correlated with severe pulmonary fibrosis in systemic sclerosis patients (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging evidence that augmentation of DNA repair mechanisms may prolong lifespan and protect against aging-related disease (Baker et al 2013). Microsatellite instability and loss of heterozygosity (LOH) are more frequent in IPF (Vassilakis et al 2000; Ricci et al 2013). LOH at the homeodomain-interacting protein kinase 2 (HIPK2) gene, which is typically activated by genotoxic stimuli, was reported to underlie apoptosis resistance, specifically of IPF fibroblasts (Ricci et al 2013).…”
Section: Genomic Instabilitymentioning
confidence: 99%
“…Further details are reported in a previous study (Ricci et al, 2013). For detection, an ECL chemiluminescence system (Therma Scientific) was used.…”
Section: Immunoblotsmentioning
confidence: 99%